Preparing health care providers for disaster response-experience from selected countries - Ahayalimudin, Nurul'Ain; W.P, Sharifa Ezat; A, Siti Nurul Akma (International Research Journal, 2012)
Introduction: Disaster occurs unexpectedly, without warning. Health care providers (HCPs) as a front-liner in providing health services to the affected population shall e prepared with the knowledge and skills in response to disaster and managing disaster victims effectively. Objective: The purpose of this article is to identify experience of selected countries in preparing HCPs for managing the disaster. Methodology: English language articles on disaster response among health care providers were reviewed, focusing on United States of America and Japan, and literature search via electronic databases which were identified using keywords. Findings: Japan is known as well-prepared country in the world in terms of disaster management. However, during Great Eastern Japan Earthquake hits recently, the country unable to manage appropriately due to central government seems stunned and slow to respond as the events comes one to another in a short time. The similar situation occurs in U.S. whereby the government requires local and state organizations to adopt the federal incident command. It is recommended that better national government disaster coordination agency is required, as well as improvements at the local authority levels and there should e a single agency for handling all disasters at every government level. Conclusion: Despite habitually struck by disaster, Japan and U.S remain not fully prepared as disasters occur unpredictable. However, literature showed that both countries actively prepared their HCPs in terms of disaster-related education and training localizes their disaster response and integrate with the private sector. many health care organization and universities had established education and training program as to equip their HCPs with disaster management training program as a result to reduce death toll and minimize aftermath of the disaster. Keywords: Disaster; disaster response; disaster preparedness; Japan Earthquake; Health care providers